Determinants of Economic Growth in Gulf Cooperation Council (GCC) Countries - Mohammad Haidar Risyad; Imron Mawardi (Universitas Airlangga, 2023)
ABSTRACT: This study aims to determine to determine the development of Islamic finance, financial development, government governance, and population growth on economic growth in the six GCC member countries (Bahrain, Kuwait, Qatar, Oman, Saudi Arabia, and the United Arab Emirates) during the period 2013 to 2019. This study uses a quantitative approach, pooled least success (PLS) analysis, and the classical assumption test. The results of this study indicate that the development of Islamic finance, government governance, and population growth can significantly contribute to economic growth. In addition, this research contributes to the previous literature, especially in indicators measuring the development of Islamic finance and empirical evidence that the development of Islamic finance, institutional quality, and population growth can drive economic growth. Keywords: Economic Growth, GCC Countries, Islamic Financial Development, Country Governance, population growth ABSTRAK: Tujuan penelitian adalah untuk mengetahui dampak perkembangan keuangan Islam, perkembangan keuangan, tata kelola pemerintah, dan pertambahan penduduk terhadap pertumbuhan ekonomi di enam negara anggota GCC (Bahrain, Kuwait, Qatar, Oman, Arab Saudi dan Uni Emirat Arab) selama periode 2013 sampai 2019. Penelitian ini menggunakan pendekatan kuantitatif dan analisis pooled least suqares (PLS) beserta uji asumsi klasik. Hasil penelitian ini menunjukkan bahwa perkembangan keuangan Islam, tata kelola pemerintah, dan pertumbuhan penduduk mampu memberikan kontribusi yang signifikan terhadap pertumbuhan ekonomi. Selain itu, penelitian ini berkontribusi terhadap literatur sebelumnya, khususnya dalam hal indikator pengukuran perkembangan keuangan Islam dan bukti empiris bahwa perkembangan keuangan Islam, kualitas kelembagaan, dan pertumbuhan penduduk mampu mendorong pertumbuhan ekonomi. Kata Kunci: Pertumbuhan ekonomi, Negara-Negara GCC, Perkembangan Keuangan Islam, Tata Kelola Pemerintah, pertumbuhan penduduk